Decentralisation and forests resources in Indonesia: removing institutional constraints and redesigning policies for better future - Djogo, A.P.Y. (ATSE Crawford Fund, 2002)
The political transformation in Indonesia, followed by administrative decentralisation through the provision of regional autonomy, has had catastrophic consequences. The decentralisation of forest resource governance and management has engendered a parallel decentralisation of moral hazards such as opportunistic behaviour, abuse of power and uncontrolled markets. Forestry sector policies neither facilitate nor support community-based forest resource management, nor forest conservation and restoration. This paper analyses the current situation in forest resource exploitation from institutional perspectives. The analysis is based on case studies from two sites in Indonesia and consultation with stakeholders in various hierarchies. It identifies key points that institutions should observe in the decentralisation process to secure better performance or outcomes in forest resource management. In addition to removing institutional constraints, it is argued that policies need to be redesigned. This paper concludes with recommendations to remove institutional constraints and to redesigning policies.